2021
DOI: 10.1002/osp4.507
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the commercial determinants of dietary behaviors associated with obesity: A systematic review using principles from critical interpretative synthesis

Abstract: Introduction Unhealthy diet is an important preventable risk factor for overweight and obesity. Identifying the key drivers of an unhealthy diet is an important public health aim. “Big Food” has been identified as an influential factor shaping dietary behavior and obesity, and their practices have broadly been labeled as the “commercial determinants of obesity,” but there is a lack of definitions and conceptualizations for these terms. This review aimed to synthesize literature on the commercial determinants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 109 publications
(539 reference statements)
0
20
0
Order By: Relevance
“…The global increase in childhood obesity 1 coincides with the marked increases in the food and beverage industry's budget for marketing aimed at children 2 . Of the various ways in which commercial determinants influence health, 3 marketing and preference shaping is used especially often to target children and adolescents 4 . From a marketing perspective, this makes sense because children are more susceptible to media and marketing influences than adults, and once a child has developed a preference for a food or brand, they may remain a lifelong buyer 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global increase in childhood obesity 1 coincides with the marked increases in the food and beverage industry's budget for marketing aimed at children 2 . Of the various ways in which commercial determinants influence health, 3 marketing and preference shaping is used especially often to target children and adolescents 4 . From a marketing perspective, this makes sense because children are more susceptible to media and marketing influences than adults, and once a child has developed a preference for a food or brand, they may remain a lifelong buyer 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 Of the various ways in which commercial determinants influence health, 3 marketing and preference shaping is used especially often to target children and adolescents. 4 From a marketing perspective, this makes sense because children are more susceptible to media and marketing influences than adults, and once a child has developed a preference for a food or brand, they may remain a lifelong buyer. 5 Indeed, several systematic reviews demonstrated the effectiveness of food marketing through different media channels, for example, television or the Internet, on children's food attitudes, preferences, and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…However, conceptualizations of the commercial determinants of dietary behaviors and obesity also point to more indirect ways of influencing dietary behaviors. 2 , 35 These strategies in the political and legal spheres include framing the evidence and debate, such as in the media or public consultations 36 influencing the policymaking process, such as lobbying against a sugar tax, 37 and limiting corporate liability, such as keeping prices low so that they do not reflect the true costs of the damage caused by consumption. 38 Future studies and systematic reviews could substantiate these conceptualizations with empirical evidence to further strengthen the evidence base on the commercial determinants of oral health.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly because traditional evidence models have been criticised for being ill-suited to account for the “real-life” contexts in which health decisions are made and the broader systems in which policies and interventions take place [ 3 , 4 ]. Therefore, a “complex systems approach” has been advocated as a way of understanding the many influential factors and different sectors, and their interactions that affect complex health issues like diet and obesity [ 5 ]. Incorporating systems thinking methods into policymaking has the potential to increase policy efficacy and better anticipate unintended consequences of well-intentioned practices from other contexts [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The commercial determinants of obesity are strategies used by the food and beverage industry to produce, promote and increase the sales of their products, sometimes at the expense of public health, especially where their promotion strategies particularly target children and adolescents with foods high in salt, fats, sugar and energy density through integrated marketing techniques [ 5 ]. Incorporating systems thinking can actively foster dialogue between diverse stakeholders and enlighten the mechanisms by which commercial drivers influence core dietary behaviour and can affect health a long time into the future.…”
Section: Introductionmentioning
confidence: 99%